Optimal and Quasioptimal Algorithms of Distinction of the Compressed Images in Bases of Orthogonal Polynomials - Chernoyarov, Oleg Vyacheslavovich; Breznan, Martin (Communications - Scientific letters of the University of Zilina, 2012)
The synthesis and analysis of effective practically realized algorithms of distinction of signals and images represented in bases of orthogonal polynomials was executed. Influence of distortions at formation of sensed and reference useful signals was considered. Recommendations about application of the synthesized distinction algorithms were formulated.